2015
DOI: 10.1074/jbc.m115.642884
|View full text |Cite
|
Sign up to set email alerts
|

hMSH5 Facilitates the Repair of Camptothecin-induced Double-strand Breaks through an Interaction with FANCJ

Abstract: Background: Camptothecin induces replication-associated DSB formation. Results: hMSH5-FANCJ facilitates the repair of camptothecin-induced DSBs. Conclusion: Functional interplay between hMSH5 and FANCJ is involved in replication stress-induced DSB repair. Significance: Understanding the mechanisms of DSB repair, induced by replication stress, is pivotal to develop new anticancer targets and therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
(75 reference statements)
0
10
0
1
Order By: Relevance
“…Confounding this suggestion, however, is the observation that loss of BLM helicase in mouse meiosis is associated with increased COs (Holloway et al 2010), while others have suggested that BLM and FANCJ may act coordinately in mitotic cells to unwind DNA at the end of a DSB and thereby to suppress repair by HR (Xu et al 2015). The upregulated BLM localization through prophase I is similar to that seen in mutants lacking the class II crossover regulator, MUS81 (Holloway et al 2008), suggesting that BLM participates in recruiting additional MLH1-MLH3-mediated crossover events in the absence of either MUS81 or FANCJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confounding this suggestion, however, is the observation that loss of BLM helicase in mouse meiosis is associated with increased COs (Holloway et al 2010), while others have suggested that BLM and FANCJ may act coordinately in mitotic cells to unwind DNA at the end of a DSB and thereby to suppress repair by HR (Xu et al 2015). The upregulated BLM localization through prophase I is similar to that seen in mutants lacking the class II crossover regulator, MUS81 (Holloway et al 2008), suggesting that BLM participates in recruiting additional MLH1-MLH3-mediated crossover events in the absence of either MUS81 or FANCJ.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that FANCJ interacts with the MutS homolog, MSH5 (Xu et al 2015). MSH5 is a component of the MutSγ complex alongside MSH4, which functions as an essential regulator of the predominant crossover pathway during prophase I (Hollingsworth et al 1995; Kneitz et al 2000; Paquis-Flucklinger et al 1997; Ross-Macdonald and Roeder 1994; Snowden et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the hMSH5 C85T polymorphism poses an increased risk of sperm DNA damage and male infertility in Chinese populations (Xu et al, 2010;Ji et al, 2012). Given the fact that hMSH5 is expressed in primary and cancer cells and the expression of hMSH5 can be induced by radiation treatment (Tompkins et al, 2009;Xu et al, 2015), it is conceivable that radiation-induced DNA lesions in germ cells may not be properly repaired on the hMSH5 P29S background, thereby leading to a long-lasting effect on spermatogenesis. The current observations warrant future exploration of the potential effect of hMSH5 on DNA damage repair in spermatogonial stem cells.…”
Section: Discussionmentioning
confidence: 74%
“…With no surprise, many genes involved in SSB and DSB repair are on the list, such as PARP1, XRCC1, PNKP, TDP1 for SSB repair; MRN, ATM-CHK2, ATR-CHK1 for DSB signaling; BRCA1/2, XRCC2, XRCC3 for HR. Most recently, the hMSH5-FANCJ complex has also been implicated to play a role in CPT-induced DNA damage response and repair [ 64 ]. Mutations in the binding partners of these repair factors are also likely to sensitize cells to CPT treatment.…”
Section: Pathways Involved In the Repair Of Cpt-induced Dna Lesionmentioning
confidence: 99%